Treatment of facial rejuvenation with fat restoration - Seyed Reza Mousavi (Dove Medical Press, 2010)
Seyed Reza MousaviSurgical Department, Shohada Medical, Center, Shahid Beheshti University of Medical Sciences, Tajrish, Tehran, IranObjective: To improve the compensation for fat atrophy and making the face look young and improve the mental and emotional conditions of patients.Material and methods: Our study was done from April 2003 to March 2006 with an assessment and documentation of the degree of facial lipoatrophy.Results: We have very good results in 91% of patients with no important complications.Discussion: Treatment of facial lipoatrophy is justified to overcome the physical and social consequences of facial fat loss that occur as a natural part of aging.Keywords: facial rejuvenation, facial lipoatrophy, aging